Evaluation of physicochemical and microbiological quality of drinking water in the distribution system of Dharan, Nepal - Khatiwada, Aasara; Chaudhary, Asmita; Limbu, Dhiren Subba; Maharjan, Bijaya Laxmi (Himalayan Journal of Science and Technology, 2022)
Dharan has been facing drinking water-related problems for a very long time now and this research was conducted in order to determine whether the quality of water being distributed throughout the city was one of them. Hence, 31 samples were taken from the drinking water distribution system of Dharan in the spring of 2022 for evaluating the physicochemical and microbiological quality of drinking water being distributed across the sub-metropolitan city. Though public knowledge and adequate management of watershed and reservoir premises were insufficient, the physicochemical characteristics were determined to be within the National Drinking Water Quality Standards (NDWQS) for drinking water with temperatures ranging from 23.6 °C to 25.6 °C, pH 7.7 to 8.5, conductivity 38.2 to 38.7 µS/cm, Dissolved Oxygen (DO) 7.7 to 9.0 mg/L, Biological Oxygen Demand (BOD) 0.8 to 1.8 mg/L, chloride 29.82 to 34.08 mg/L, nitrite 10 mg/L and ammonia